Language teachers and teaching : global perspectives, local initiatives - Ben Said, Selim (Routledge research in education., 2013)
This volume gathers contributions from a range of global experts in teacher education to address the topic of language teacher education. It shows how teacher education involves the agency of teachers, which forms part of their identity, and which they take on when integrating into the teaching community of practice. In addition, the volume explores the teachers' situated practice--the dynamic negotiation of classroom situations, socialization into the professional teaching culture, and ""on the ground experimentation"" with pedagogical skills/techniques